1960
DOI: 10.1002/j.1538-7305.1960.tb03957.x
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance of Ultraprecise 2.5-mc Quartz Crystal Units

Abstract: A 2.5-mc crystal unit has been developed for use in a new, extremelu stable frequrncy standard oscillator. A well-balanced design was achieved by using a 30-mm-diameter, plano-conoex, polished quartz plate, coated with gold and operated on its fifth ooertone. The quartz plate is mounted on its quiescent edge in an eoacuaied bulb, and achieoes a Q of five to six million, represeniaiioe of the Q of the quartz itself. The temperature coefficient, current coefficient, frequency adjustmen: tolerance and frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1962
1962
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…These simulation results are in good agreement with the results found in the literature for quartz [17] and for GaP04 [5].…”
Section: A Internal Friction Behaviorsupporting
confidence: 91%
“…These simulation results are in good agreement with the results found in the literature for quartz [17] and for GaP04 [5].…”
Section: A Internal Friction Behaviorsupporting
confidence: 91%
“…Of particular interest is the resonator quality factor -frequency product, Qf; the best value we have measured to date is 13.4 million for LGS and 16.0 million for LGT. Interestingly enough, this latter value is equal to the asymptotic value for natural quartz AT quartz resonators measured by Warner [24].…”
supporting
confidence: 51%
“…The maximum obtainable value for a given orientation and mode of vibration of a piezoelectric material constitutes a figure of merit for the material. This measure appears to have been introduced by Warner [24] in 1960. For resonators using AT-cut natural quartz, Warner obtained an estimated upper bound for Q.f of 16.106 based on measurements of carefully made resonators over a frequency range from a few hundred kilohertz to 100 MHz.…”
Section: Quality Factormentioning
confidence: 98%
“…Some 30 years ago Bommel [52] and later Warner [53] have shown that a material limit for AT-cuts reveals a dependence Q, * x, = 1.5 x 10" (74) whereas Seed has found for BT-cuts a two-times-larger value [54]. Recently Bidart and Chauvin [55] We have plotted all four relations (74)-(77) in Fig.…”
Section: Resonatorsmentioning
confidence: 93%